(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
This research is designed to examine the relationship between the capital structure and profitability of non-financial firms in Bosnia and Herzegovina during the period of ten years, from 2003-2012. The goal is to prove the existence of the relationship between the firm’s capital structure choice and its profitability. The analysis is extended by including the debt structure and differentiating between the types of debt such as the long-term and the short-term ones. The results of the multivariate canonical correlation analysis provide support to a hypothesis that the capital structure and profitability have statistically significant relationships. Furthermore, the findings provide support that firms develop different patterns of profitability depending on the capital structure choice. We found that an increasing proportion of short-term debt and long-term debt in the overall liability of the firm reduces its profitability. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.